Peculiarities of rehabilitation of persons in acute and early period of spine-spinal injury - Gorishchak, S. P. (Journal of Education, Health and Sport, 2016)
The article presented deals with the problem of rehabilitation of persons in acute and early periods of spine and spinal cord injury inUkraine. The author draws attention to the urgency of this problem in today. In the work the analysis of modern researches in the field of medical and psychological support of patients of acute and early spinal cord and spinal cord injury is given. The main markers of the direction of work with persons who experience acute and early periods of spine and spinal cord injury are indicated.